Research on Marketing Problems and Optimization Strategies of ByteDance in the Era of Big Data - Liu Yan (SHS Web of Conferences)
With the advent of the big data era, industries across the board are encountering both opportunities and challenges in their efforts to transform and upgrade. In the realm of marketing, the discussion around the transformation of Internet products remains relatively sparse. This article focuses on ByteDance, a prominent Internet company known globally for its flagship product, TikTok, to explore how companies in this sector can leverage big data for marketing success. While TikTok has achieved significant popularity, ByteDance faces multiple challenges that threaten its market position. These include increasing governmental scrutiny over data security, intensified competition in the short video market, and growing societal concerns about underage addiction to digital content. Additionally, ByteDance has struggled to diversify its revenue streams, relying heavily on TikTok’s success. To address these challenges, this paper proposes strategic solutions, including enhanced public relations efforts, algorithm optimization, the establishment of robust systems for underage protection, and the integration of business operations. These strategies not only aim to stabilize ByteDance’s market standing but also offer valuable insights for the broader Internet industry, highlighting the critical importance of adapting marketing strategies in an era dominated by big data.